Cardiovascular variability as a function of sleep–wake behaviour in narcolepsy with cataplexy. (6th December 2012) - Silvani, Alessandro; Grimaldi, Daniela; Barletta, Giorgio; Bastianini, Stefano; Vandi, Stefano; Pierangeli, Giulia; Plazzi, Giuseppe; Cortelli, Pietro
Summary Hypocretin/orexin signalling varies among sleep–wake behaviours, impacts upon cardiovascular autonomic control and is impaired in patients with narcolepsy with cataplexy (NC). However, evidence concerning disturbed cardiovascular autonomic control in NC patients is contrasting, and limited mainly to waking behaviour. We thus investigated whether control of cardiovascular variability is altered in NC patients during wakefulness preceding sleep, light (1–2) and deep (3–4) stages of non‐rapid eye movement (NREM) sleep and rapid eye movement (REM) sleep. Polysomnographic recordings and finger blood pressure measurements were performed on nine drug‐free male NC patients and nine matched healthy control subjects during spontaneous sleep–wake behaviour in a standardized laboratory environment. Indices of autonomic function were computed based on spontaneous fluctuations of systolic blood pressure (SBP) and heart period (HP). During wakefulness before sleep, NC patients showed significant decreases in indices of vagal HP modulation, cardiac baroreflex sensitivity and amplitude of central autonomic (feed‐forward) cardiac control compared with control subjects. During NREM sleep, the negative correlation between HP and subsequent SBP values was greater in NC patients than in control subjects, suggesting a greater contribution of central autonomic commands to cardiac control. Collectively, these results provide preliminary evidence that autonomic control of cardiac variability by baroreflex and central autonomic (feed‐forward) mechanisms is altered in NC patients during spontaneous sleep–wake behaviour, and particularly during wakefulness before sleep.